Fruit of the orchard : reading Catherine of Siena in late medieval and early modern England - Brown, Jennifer N. (Jennifer Nancy) (University of Toronto Press, 2019)
"Fruit of the Orchard sheds light on how Catherine of Siena served as a visible and widespread representative of English piety becoming a part of the devotional landscape of the period. By analyzing a variety of texts, including monastic and lay, complete and excerpted, shared and private, author Jennifer N. Brown considers how the visionary prophet and author was used to demonstrate orthodoxy, subversion, and heresy. Tracing the book tradition of Catherine of Siena, as well as investigating the circulation of manuscripts, Brown explores how the various perceptions of the Italian saint were reshaped and understood by an English readership. By examining the practice of devotional reading, she reveals how this sacred exercise changed through a period of increased literacy, the rise of the printing press, and religious turmoil."--